COVID19 Data Donation Survey Methodology Summary - Redmiles, Elissa M.; Krumm, John (Microsoft, 2020)
Survey methodology report for survey results reported in "Altruistic Data-Sharing is a Way Forward for Coronavirus Apps?", Wired 2020. Report summarizes methodology for two surveys about data donation during the coronavirus pandemic conducted by Microsoft Research.